Three new records of Megaspilidae (Hymenoptera, Ceraphronoidea) from Iran - M. Atbaei; N. Saghaei; M. Fallahzadeh (نامه انجمن حشره‌شناسی ایران, 2018)
In the present study, thirty specimens of Megaspilidae (Hymenoptera, Ceraphronoidea) were collected by Malaise-traps from different area of Fars province in southern Iran. Three species namely, Dendrocerus laticeps (Hedicke, 1929), D. perlucidus Alekseev, 1983 and Conostigmus fasciatipennis Kieffer, 1907 are new records for Iran.